FRI0450 The need for a cross-sectorial approach to facilitate work and social participation of women with rheumatoid arthritis. (23rd January 2014) - Prodinger, B.; Shaw, L.; Laliberte-Rudman, D.; Stamm, T.
Abstract : Background: Despite significant advancements toward early and comprehensive treatment for people with rheumatoid arthritis (RA) over the past couple of decades, people with RA are still likely to experience pertinent limitations in their work and social participation, and have to adapt and adjust to a life with a chronic disease. The limitations have not only impact on the individual, but also on society. The societal impact points to direct costs for comprehensive treatment, and indirect costs due to work-absenteeism and invalidity. Objectives: One of the study objectives was to disclose the intersection of arthritis-related health care and labor-market related services as relevant for Austrian women with RA, who are of employable age. Methods: An institutional ethnography was conducted that allows mapping out relations that rule organizational practices. Multiple methods (interviews, participant observations, and textual analysis of hospital records and agreements of individuals with the labor market office) were used for data collection. Analysis was performed in two stages: first, a comprehensive account about what women actually do at the conjunction with service providers in arthritis-related health care and at the labor market office; secondly, texts that mediate these interactions were analyzed to understand concepts that rule these interactions. Results: Seven Austrian women with RA, aged between 28 and 41, and varying working and living conditions were recruited for this study. The interaction in arthritis-related health care is ruled by biomedical concepts and categories. This has historically grown out of a diagnostic-related group model for funding health care. On the other hand, employment-related matters are dealt with at the labor market office and are ruled by concepts related to eligibility of benefits based on previous records of employment, employability, and willingness to work. In particular the chronic and fluctuating nature of RA is inadequately addressed by concepts of employability. Separation of health care and labor-market related services is characterized by different administrative and conceptual approaches: namely a focus on disease in health care and on employability in labor-market related services that may lead to social and participation disparities for women with RA. Conclusions: More effort is needed to bridge the structural issues that challenge women with RA to navigate the health and labor systems and to manage health and equitably participate in work life. As exemplified by this study, a cross-sectorial approach in research and practice becomes increasingly important to fully facilitate work and social participation of people with RA who are of employable age. Disclosure of Interest: None Declared